Individual differences in bilingual experience modulate executive control network and performance: behavioral and structural neuroimaging evidence. Issue 2 (11th March 2021) - Gallo, Federico; Novitskiy, Nikolay; Myachykov, Andriy; Shtyrov, Yury
Abstract: Dual/multiple language use has been shown to affect cognition and its neural substrate, although the replicability of such findings varies, partially due to neglecting the role of interindividual variability in bilingual experience. To address this, we operationalized the main bilingual experience factors as continuous variables, investigating their effects on executive control performance and neural substrate deploying a Flanker task and structural magnetic resonance imaging. First, higher L2 proficiency predicted better executive performance. Second, neuroimaging results indicated that bilingualism-related neuroplasticity may peak at a certain stage of bilingual experience and eventually revert, possibly following functional specialization. Importantly, experienced bilinguals optimized behavioral performance independently of volumetric variations, suggesting a degree of performance gain even with lower GMV. Hence, the effects of bilingualism on cognition may evolve with experience, with improvements in functional efficiency eventually replacing structural changes. We conclude that individual differences in bilingual experience modulate cognitive and neural consequences of bilingualism.